2013
DOI: 10.3892/or.2013.2798
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated inhibition of USP39 suppresses the growth of breast cancer cells in vitro

Abstract: Worldwide, breast cancer is the most frequently diagnosed life-threatening cancer in women and is the leading cause of cancer-related mortality among women. It is extremely rare but highly lethal in men. The deubiquitinating enzyme USP39 plays important roles in mRNA processing, and our previous data showed that high levels of USP39 are selectively present in different types of human breast tumor cells. The potential of USP39 as a therapeutic target for breast cancer was investigated. The expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 29 publications
10
39
1
Order By: Relevance
“…The present observations are consistent with the recent discovery that endogenous shRNA expression is enhanced by miRNAs (30,31). However, it is important to note that conventional stem-loop shRNAs, such as those used previously in lentiviruses (18), are not processed into functional siRNAs under certain conditions. The inducible expression of transgenes provides an improved level of safety since it avoids much of the unintended consequences of viral vector-mediated delivery and gene silencing.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The present observations are consistent with the recent discovery that endogenous shRNA expression is enhanced by miRNAs (30,31). However, it is important to note that conventional stem-loop shRNAs, such as those used previously in lentiviruses (18), are not processed into functional siRNAs under certain conditions. The inducible expression of transgenes provides an improved level of safety since it avoids much of the unintended consequences of viral vector-mediated delivery and gene silencing.…”
Section: Discussionsupporting
confidence: 80%
“…We found that suppression of USP39 in TNBC cell lines was key to their capacity for growth. Transient shRNA silencing by the USP39 lentivirus in MCF-7 cells partially recapitulated the aggressive basal phenotype (18). These effects on migration were independent of cell replication.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Some more recent studies have reported the involvement of USP39 in malignant cell growth. Wang et al [16] have reported that USP39is overexpressed in breast cancer, and is involved in the tumorigenesis. Wen et al [17] have reported that USP39 is a target of SUMOylation specific protein (SENP) in the proliferation of PCa cells.…”
Section: Introductionmentioning
confidence: 99%